Pac-Man championship edition 2 + arcade game series. - Microsoft Corporation; Namco Bandai Games (Firm) (Santa Clara, CA Bandai Namco Entertainment America Inc., 2016)
Featuring eye-popping 3D graphics and funky visuals, the latest version of the classic game takes chomping and chasing through mazes to a whole new level! Pac-Man: Move Pac-Man to eat all the Pac-Dots, while avoiding the ghosts, to advance to the next stage. Eat a Power Pellet to turn the tables on the ghosts and rack up a huge score! Galaga: Move the fighter and destroy the waves of incoming aliens in this space-age shooter. Dig dug : Dig up, down, left, and right and burrow through the earth. Inflate and pop enemies with your harpoon to defeat them, or squish them with a rock. Lure enemies into a tunnel and crush several at once for massive points!
Pac-Man championship edition -- Galaga -- Pac-Man -- Dig dug.
Title from disc label.
Single player.
"Microsoft"--Disc surface.
ESRB rating: E (Everyone).
System requirements: Xbox One game system; up to 5 GB storage required; additional storage, hardware, and Xbox Live may be required for setup, some updates and features.
Online requirements: broadband Internet (ISP fees apply) and Microsoft account required; in supported games, Xbox Live paid subscription required for online multiplayer.
Keywords: Pac-Man (Game) -- Computer games; Xbox video games; Video games; Xbox video games; Computer games